Ethical leadership and green innovation: the mediating role of green organizational culture - Sengullendi, Muhammet Fatih; Bilgeturk, Mahmut; Findikli, Mine Afacan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
Green innovation is critical for SMEs, which account for a significant part of employment and total value in many countries. The role of the leader in SMEs is one of the most discussed issues in the field of management and innovation. In this study, the role of ethical leadership and green organizational culture on green innovation was investigated in the context of Turkey with a cross-sectional research study covering 464 SMEs and using structural equation modelling. According to the findings, it was seen that ethical leadership has an important potential in terms of developing a green organizational culture in SMEs. In addition, it has been determined that green organizational culture has a mediating role between ethical leadership and green product and process innovations. As a result, suggestions are given to researchers and managers in the context of leadership and organizational culture in order to create green innovation and a sustainable work environment.
Keywords: green innovation; ethical leadership; green organizational culture; SMEs; CORPORATE SOCIAL-RESPONSIBILITY; FINANCIAL PERFORMANCE; TRANSFORMATIONAL LEADERSHIP; ENVIRONMENTAL INNOVATION; SUSTAINABLE DEVELOPMENT; ECO-INNOVATION; BUSINESS; STRATEGY; MODEL; ANTECEDENTS; Development Studies; Public Administration